BIOCHEMICAL COMPOSITION AND NUTRITIONAL EVALUATION OF BARLEY RIHANE (HORDEUM VULGARE L.) - Lahouar, Lamia; Ghrairi, Fatma; Arem, Amira El; Medimagh, Sana; Felah, Mouledi El; Salem, Hichem Ben; Achour, Lotfi (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Many experimental studies have suggested an important role for barley Rihane(BR)in the prevention ofcolon cancer and cardiovascular diseases. The objective of this study was to evaluate the physico-chemical propertiesand nutritional characterizations of BR compared to other varieties grown in Tunisia (Manel, Roho and Tej).Material and Methods: Total, insoluble and soluble dietary fiber(β-glucan),total protein, ash and some minerals of BRand Tunisian barley varieties were determined.Results: The results revealed that BR is good source of dietary fiber mainly β-glucan compared to the other varieties.This variety is a relatively rich source of phosphorous and potassium and it contains many important unsaturated fattyacids. BR has higher nutritional value than other varieties.Conclusion: Barley Rihane has significant nutritional characterizations compared to others Tunisian barleys varieties.